HgCdTe barrier infrared detectors. (May 2016) - Kopytko, M.; Rogalski, A.
Abstract: In the last decade, new strategies to achieve high-operating temperature (HOT) detectors have been proposed, including barrier structures such as nBn devices, unipolar barrier photodiodes, and multistage (cascade) infrared detectors. The ability to tune the positions of the conduction and valence band edges independently in a broken-gap type-II superlattices is especially helpful in the design of unipolar barriers. This idea has been also implemented in HgCdTe ternary material system. However, the implementation of this detector structure in HgCdTe material system is not straightforward due to the existence of a valence band discontinuity (barrier) at the absorber–barrier interface. In this paper we present status of HgCdTe barrier detectors with emphasis on technological progress in fabrication of MOCVD-grown HgCdTe barrier detectors achieved recently at the Institute of Applied Physics, Military University of Technology. Their performance is comparable with state-of-the-art of HgCdTe photodiodes. From the perspective of device fabrication their important technological advantage results from less stringent surface passivation requirements and tolerance to threading dislocations.